Lebanon : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2006)
Lebanon recovered from the financial shock triggered by Prime Minister Hariri's assassination. Executive Directors supported the strategy of debt reduction through sustained fiscal adjustment. They welcomed the proactive stance of banking sector supervision and encouraged adoption of a strong securities regulator with adequate legal protection to enhance the stability of the stock market. They stressed the need to strengthen the environment for private sector activity by reducing red tape and corruption, reactivating the liberalization and privatization of the telecom sector, strengthening contract enforcement, and accelerating structural reforms.